Self-assessment practices: an empowering tool in the teaching and learning EFL processes - Rodríguez Ochoa, Edgar Orlando (Colombian Applied Linguistics Journal, 2007)
Evaluating the students’ language learning process requires a lot of analysis and reflection. Although some research has been conducted to observe the way teachers use assessment practices in diverse educational contexts, I consider there needs to be more research in order to examine how assessment practices are carried out in our educational context. This article presents a pedagogical project carried out in a higher education institution with EFL learners. It focuses on the implementation of self-assessment practices conducted in the context of the project followed by some preliminary results that I have encountered.